Read the following calculations:

$$\\a=b\\

a\times a= a\times b\\

a^2=ab\\

a^2+a^2=a^2+ab\\

2a^2=a^2+ab\\

2a^2-2ab=a^2+ab-2ab\\

2a^2-2ab=a^2-ab\\

2a^2-2ab=1a^2-1ab\\

2(a^2-ab)=1(a^2-ab)\\

2=1$$

Can you spot the miscalculation ?

EinsteinJr Apr 30, 2015

#7**+5 **

For those who haven't understood, the miscalculation is on the penultimate line :

Since a²=ab, a²-ab=0;

And in the 9th line, I divided each side by a²-ab, so I divided by 0; and as you must now, the division by 0 is impossible.

EinsteinJr May 1, 2015

#1**0 **

a=b

axa=axb

a^2=ab

a^2+a^2=a^2+ab

a^4=a^2+ab

2a^2-2ab=a^2-ab

2a^2-2ab=1a^2-1ab

the correct answer is to this part is: 2a^2-2ab=a^2-ab

so the final answer is a=square root of ab

Guest Apr 30, 2015

#7**+5 **

Best Answer

For those who haven't understood, the miscalculation is on the penultimate line :

Since a²=ab, a²-ab=0;

And in the 9th line, I divided each side by a²-ab, so I divided by 0; and as you must now, the division by 0 is impossible.

EinsteinJr May 1, 2015